The beauty of intimacy : lens and paper. - Balth, Carel; Locher, Hans; Gemeentemuseum, Den Haag (Den Haag : Gemeentemuseum Den Haag, 2000)
Ahtila, Eija-Liisa ; Antezzo, Matthew ; Balth, Carel ; Beecroft, Vanessa ; Bond, Henry ; Van Caeckenbergh, Patrick ; Cattelan, Maurizio ; Daniels, René ; Dolven, A.K. ; Dumas, Marlene ; Dijkstra, Rineke ; Fairhurst, Angus ; Framis, Alicia ; François, Michel ; van Golden, Daan ; Gordon, Douglas ; Halley, Peter ; Hempel, Lothar ; Hirakawa, Noritoshi ; Hirst, Damien ; Hyber, Fabrice ; Jones, Sarah ; De Keyser, Raoul ; Koelewijn, Job ; Land, Peter ; Lockhart, Sharon ; Marcaccio, Fabian ; van Meene, Hellen ; Meister, Ulrich ; Miyajima, Tatsuo ; Mori, Mariko ; Morrisroe, Mark ; Muniz, Vik ; Neshat, Shirin ; Ofili, Chris ; Opie, Catherine ; Orozco, Gabriel ; Owens, Laura ; Pardo, Jorge ; Pettibon, Raymond ; Peyton, Elizabeth ; Prince, Richard ; Rist, Pipilotti ; Samore, Sam ; Sander, Karin ; Schneider, Anne-Marie ; Schorr, Collier ; Smith, Kiki ; Struth, Thomas ; Sugimoto Hiroshi ; Tandberg, Vibeke ; Tillmans, Wolfgang ; Tiravanija, Rirkrit ; Trockel, Rosemarie ; Tuymans, Luc ; van Warmerdam, Marijke ; Wearing, Gillian ; Whiteread, Rachel ; Yanagi, Yukinori
lijst v.d. werken p. 169-175
Engels
The beauty of intimacy, Gemeentemuseum Den Haag, 10.02 - 15.04.2001
boek